PROGRAM PENDIDIKAN KESEHATAN PADA MASYARAKAT PESANTREN AL AMIN KOTA TASIKMALAYA - Asep Riyana; Kusmiyati; Mamat Purnama (Jurnal Pengabdian Masyarakat DEDIKASI, 2022)
Maintenance of personal hygiene is an important thing that must be done by everyone. Personal hygiene can determine health status. . If skin health is not maintained, it will cause skin diseases caused by fungi, viruses, germs and parasites, one of the diseases that is often found in skin diseases is scabies. (Nursing, 2013). Scabies is identical to a disease in humans who live in a community such as a boarding school, this happens because of poor hygiene conditions, poor sanitation and room conditions that are not exposed to direct sunlight. Scabies spreads quickly in a community that lives together so that treatment must be carried out simultaneously and thoroughly on all people and the environment affected by scabies, because if treatment is carried out individually, it will be easy to re-infect scabies (Djuanda, 2017). The assumption that has developed in the community is that Islamic boarding schools are slum places, with unhealthy environmental conditions. Scabies disease is often found in Islamic boarding schools because Islamic boarding school children / santri often exchange clothes or borrow clothes from each other, gloves and even pillows, rarely take a bath, towels and toiletries such as soap. So that the rate of transmission of scabies also increases. Transmission occurs because the female Sarcoptes scabei is fertilized. Lack of attention to Islamic boarding schools including elements in it, namely the students make Islamic boarding schools a place that is considered a nest of disease due to the lack of knowledge of students about this scabies disease. The factors that underlie a community environment such as boarding schools are often infected with scabies, namely because of the dense environment, limited knowledge of students about scabies and students' awareness of the importance of maintaining personal and environmental hygiene. From the puskesmas data in 2019 the incidence of scabies in the Al Amin Islamic boarding school was high with the number of students infected with 52 people and those not infected with 47 people. From the results of Purnimarahmi's research (2016) regarding the level of knowledge of the students, the following results showed that students' knowledge of the disease Most of the scabies in the Al-Amin Islamic Boarding School in Tasikmalaya City were in the less category, namely 79.2%. And the results of Novita's research (2016) from 62 respondents stated that the risk factor for the occurrence of scabies disease in RSUD dr. Soekarjo majority 65.1% male, 41.3% aged 13-21 years, 73.02% environmental factors in the moderate category and 34.9% suffered by students. This activity aims to increase knowledge of students, the method is carried out in the form of health education lectures, question and answer discussions, with advocacy strategies, atmosphere building and community empowerment at Al Amin Islamic Boarding School in Tasikmalaya City.